Cement-in-cement femoral component revision in the multiply revised total hip arthroplasty: results with a minimum follow-up of five years. (February 2017) - Sandiford, N. A.; Jameson, S. S.; Wilson, M. J.; Hubble, M. J. W.; Timperley, A. J.; Howell, J. R.
Abstract : Aims: We present the clinical and radiological results at a minimum follow-up of five years for patients who have undergone multiple cement-in-cement revisions of their femoral component at revision total hip arthroplasty (THA). Patients and Methods: We reviewed the outcome on a consecutive series of 24 patients (10 men, 14 women) (51 procedures) who underwent more than one cement-in-cement revision of the same femoral component. The mean age of the patients was 67.5 years (36 to 92) at final follow-up. Function was assessed using the original Harris hip score (HHS), Oxford Hip Score (OHS) and the Merle D'Aubigné Postel score (MDP). Results: The mean length of follow-up was 81.7 months (64 to 240). A total of 41 isolated acetabular revisions were performed in which stem removal facilitated access to the acetabulum, six revisions were conducted for loosening of both components and two were isolated stem revisions (each of these patients had undergone at least two revisions). There was significant improvement in the OHS (p = 0.041), HHS (p = 0.019) and MDP (p = 0.042) scores at final follow-up There were no stem revisions for aseptic loosening. Survival of the femoral component was 91.9% (95% confidence intervals (CI) 71.5 to 97.9) at five years and 91.7% (95% CI 70 to 97) at ten years (number at risk 13), with stem revision for all causes as the endpoint. Conclusion: Cement-in-cement revision is a viable technique for performing multiple revisions of the well cemented femoral component during revision total hip arthroplasty at a minimum of five years follow-up. Cite this article: Bone Joint J 2017;99-B:199–203.